Interactive Multimedia Based on Project-Based Learning Model Using Articulate Storyline 3 Application on the Topic of the Human Digestive System - Marpelin, Ni Komang Sinta; Margunayasa, I Gede; Trisna, Gusti Ayu Putu Sukma (International Journal of Elementary Education, 2023)
This development research is motivated by using media and learning models in elementary schools that could have been more optimal and decreasing student learning outcomes in elementary schools in science content. This research develops interactive multimedia based on the project-based Learning (PjBL) model using the articulate storyline of three applications on the subject of the human digestive system. Development research uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of this study were four experts, three teachers, six students, and 1 group of fifth-grade students. The object of this research was interactive multimedia based on the PjBL model. Data collection methods used are questionnaires/questions and tests. The data collection instrument was a closed questionnaire using a rating scale and multiple-choice test instruments. This development research shows that an interactive multimedia prototype based on the PjBL model consists of 3 main parts: the opening display, the initial display, and the main display. The average media expert eligibility score is 4.71, and the expert learning content is 4.8, a very good classification. The average practicality score by the teacher is 4.89, and by students is 4.78, with a very good classification and interactive multimedia based on the PjBL model using the Articulate Storyline 3 application effectively increases fifth-grade students' learning outcomes on the human digestive system.